1999
DOI: 10.1038/sj.ijo.0800814
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the proopiomelanocortin gene in Caucasians with early onset obesity

Abstract: OBJECTIVE: Mutations in the human gene encoding the polyhormone peptide proopiomelanocortin (POMC) are associated with obesity in rare cases and the gene co-localizes with a reported quantitative trait loci (QTL) for variations in circulating leptin levels and fat mass on human chromosome 2p21. In this study we have used polymerase chain reaction (PCR) and single strand conformation polymorphism (SSCP) analysis, to test whether variations in the human POMC gene are associated with human obesity. DESIGN AND SUB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 17 publications
3
38
1
Order By: Relevance
“…We found that the other two SNPs, 51 G/C and 7965 C/T, previously reported at low frequency in obese subjects, 11,16 occurred at even lower frequency in our normal female subjects: 51 G/C at 1.0% and 7965 C/T at 0.4%. The inclusion of these two rare SNPs was aimed at exposing any relatively strong effect in potential regulatory regions (51 G/C in the promoter and 7965 C/T in the 3 0 UTR) by examining a large sample.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…We found that the other two SNPs, 51 G/C and 7965 C/T, previously reported at low frequency in obese subjects, 11,16 occurred at even lower frequency in our normal female subjects: 51 G/C at 1.0% and 7965 C/T at 0.4%. The inclusion of these two rare SNPs was aimed at exposing any relatively strong effect in potential regulatory regions (51 G/C in the promoter and 7965 C/T in the 3 0 UTR) by examining a large sample.…”
Section: Discussionmentioning
confidence: 71%
“…It has been suggested that any causative mutations are more likely to occur in regulatory sequences, because coding changes could affect more than one of the overlapping cleavage products and have far-reaching effects on other physiological processes. 11 The associations of BMI, weight and total fat with SNPs in regions flanking the POMC gene exposed in this powerful study suggest that control of POMC expression may be influential in the determination of body weight. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations